2023
DOI: 10.1177/00812463231186269
|View full text |Cite
|
Sign up to set email alerts
|

Caseness and comorbidity of probable (complex) post-traumatic stress disorder and depression in survivors of genocide against Tutsi in Rwanda: the role of social determinants

Abstract: Numerous studies have been conducted among survivors of the genocide against the Tutsi on the prevalence of depression and post-traumatic stress disorder. However, thus far, no studies provide information on the frequency of comorbidity of these disorders, the prevalence of the new trauma-related diagnostic disorder known as complex post-traumatic stress disorder, and the role of social determinants, such as age, sex, marital status, employment category, education, and location, in the occurrence of these diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Several studies have identified trauma-related disorders in East African populations, including post-traumatic stress disorder (PTSD), its complex forms, depression (Mugisha et al, 2015;Familiar et al, 2016;Bapolisi et al, 2020;Mutuyimana et al, 2023) and clinical aspects of historical trauma (Mutuyimana and Maercker, 2022). However, clinical experience has shown that survivors of trauma in East Africa may present with symptoms that differ from those in the trauma-related disorder categories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified trauma-related disorders in East African populations, including post-traumatic stress disorder (PTSD), its complex forms, depression (Mugisha et al, 2015;Familiar et al, 2016;Bapolisi et al, 2020;Mutuyimana et al, 2023) and clinical aspects of historical trauma (Mutuyimana and Maercker, 2022). However, clinical experience has shown that survivors of trauma in East Africa may present with symptoms that differ from those in the trauma-related disorder categories.…”
Section: Introductionmentioning
confidence: 99%
“…Although the processes described in the context of CSTs may play an important role in clinical practice and research, they have not been explored in populations exposed to traumatic events, such as in Africa. A recent study in East Africa showed that 52% of participants did not meet criteria for probable PTSD, complex PTSD, and depression, although they had other significant clinical symptoms (Mutuyimana et al, 2023). This could be due to many factors, including assessment inadequacy and mental disorder symptoms that do not fit the East African culture.…”
Section: Introductionmentioning
confidence: 99%